Perubahan Pengetahuan dan Sikap Masyarakat Mayang-Gatak Setelah Diberi Promosi Kesehatan Jiwa pada Masa New Normal - Rosiana Danty Sukma; Arif Widodo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of providing mental health promotion in the new normal period on changes in knowledge and attitudes of the Mayang-Gatak community. This research is quantitative research with a quasi-experimental method. The results obtained from this study are that providing mental health promotion is very effective in preventing and reducing the impact of mental health decline. The conclusion from this study is that there is an influence of mental health promotion during the new normal period on changes in knowledge and attitudes of the Mayang-Gatak Sukoharjo community. Keywords: Mental Health, New Normal, Changes in Knowledge, Changes in Attitudes